Research on local deformation property of asphalt mixture using digital image correlation. (1st June 2017) - Xing, Chao; Tan, Yiqiu; Liu, Xueyan; Anupam, Kumar; Scarpas, Tom
Highlights: DIC deformation calculation with natural surface images can satisfy the precision requirement. Subset size of 31 can be selected as the optimal DIC test parameter. R 2 obtained by the least squares fitting method can identify the critical steady strain. Abstract: Failure behavior of asphalt mixture is the process of local deformation accumulation, therefore, local deformation investigation is the base work of failure behavior. Digital image correlation (DIC) method is an optical method which can calculate the local deformation in the failure process. This paper aims to evaluate the precision, select the optimal test parameters for DIC deformation measurement based on natural speckle image, and investigate the local deformation characteristic in the failure process for different mixtures. The results show the image quality of AC with smaller normal maximum aggregate size (NMAS) is better for DIC deformation calculation, the relative deviation of virtual translation and shear test can satisfy the precision requirement, the optimal subset size is 31. Based on the strain distribution, the optimal local deformation measure length for indirect tensile test is set as 50 mm, the critical steady strain is proposed based on R 2 obtained by the least squares fitting method, according to local deformation characteristic, the results show SMA can bear more deformation before unstable deformation stage and failure.